Impact Assessment of Pradhan Mantri Jan-Dhan Yojana in Augmenting Financial Inclusion in India - A District-Level Analysis - Vishal Yadav, Shishir Kumar Singh, Nirmala Velan, Md Asif Aftab, Ravi Kumar, Aman Kumar Swarnkar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study builds up a financial inclusion index (FII) across 27 Indian states’ districts utilizing UNDP’s similar approach in constructing the Human Development Index. The FII is constructed for the period 2011-2018. The study additionally investigates government schemes’ effectiveness, especially the PMJDY, in augmenting financial inclusion throughout its inception. The study’s significant finding shows that a greater part of the Indian locale falls under the class of low financial inclusion. Southern areas perform better while the central, eastern, and north-eastern locale perform poorly in financial inclusion. Further, FII and HDI have a positive association between them. Furthermore, the PMJDY framework has not driven the economy towards a high degree of financial inclusion. Only a couple of areas improve their rank from low to medium financial inclusion. Subsequently, underlying changes are legitimized in the institutional setting by fortifying and growing monetary organizations while handling digital literacy.